Levantamento gravimétrico na região de Franca - SP e delfinópolis - MG, no reconhecimento e delimitação de feições estruturais (Zonas de Sutura) - Fries, Maximilian [UNESP]; Filho, Walter Malagutti [UNESP]; Morales, Norberto [UNESP]; Dourado, João Carlos [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2007)
This paper presents the results of a geophysical study carried out in northeastern São Paulo State and southwestern Minas Gerais State over an area 80 km wide and 97.5 km long in SE Brazil. The Bouguer anomaly map, and geological and structural data allowed to identify three different gravity domains - crustal blocks limited by major discontinuities -related to the structural pattern of the area. These discontinuities were interpreted as geosuture zones underlying the Paraná Basin sediments which have extensions in the Pre-cambrian Basement. The crustal discontinuities named Alterosa and Ribeirão Preto may be seen as A - type collision sutures in a triple junction arramgement. Two prominent linear anomalies are recognized in the Bouguer anomaly map, as well as the limit between the Brasilia and São Paulo crustal blocks or paleoplates. The Alterosa suture zone trends NW-SE while the Ribeirão Preto suture has a NE-SW direction. The Bouguer anomaly map provides subsidies and information on new concepts and theories leading to the refinement of tectonic models.
Gravimetrical data in the Franca region - SP and Delfinopolis - MG, in the recognition and delimitation of the structural forms (suture areas)
Keywords: Bouguer anomaly; Geophysic; Tectonic features; crustal structure; data; geophysics; gravimetry; map; modeling; tectonics; Brazil; Minas Gerais; Ribeirao Preto; Sao Paulo [Brazil]; South America